The Digital Handshake: A Group Contract for Authentic eLearning in Higher Education - Hesterman, Sandra (Journal of University Teaching and Learning Practice, 2016)
An emerging challenge for the Australian higher education sector is the delivery of authentic eLearning to support the collaborative construction of knowledge through the provision of real-life tasks in an online environment. This paper describes research conducted in a fourth-year university course where students from across the nation were required to work in small groups to complete an online assignment task: to design a provocation that could be integrated into an early childhood learning environment to promote multiliteracies learning. A qualitative design-based study of two cohorts of students found that online group work facilitates authentic connections between educational theory and practice, and that the introduction of a ‘digital handshake’ group contract can support these processes.